Development of spontaneous and sensory evoked network activity in rodent cerebral cortex in vivo - Nigi, Elena; Yang, Jenq-Wei; Luhmann, Heiko J.; Sinning, Anne (Frontiers in Cellular Neuroscience, 2025)
Neuronal activity in the cerebral cortex comes in surprisingly early and influences or even controls a number of important developmental process like neurogenesis, neuronal migration, myelination, formation of cortical maps and local circuits, and programmed cell death. During the late prenatal and early postnatal period, the neocortical network shows a developmental transition from sparse, synchronized, low activity patterns to continuous, desynchronized, high activity patterns. This developmental sequence has been demonstrated in various neocortical areas of different mammalian species. This review article aims to provide a comprehensive overview of the early development of neuronal network activity in the cerebral cortex. We mainly focus on the rodent barrel cortex and a developmental period when the cortex gains mature functional properties at the cellular and network level. After briefly summarizing the developmental processes underlying the construction, reconstruction, and deconstruction of neocortical circuits, we describe the age-dependent changes in spontaneous and sensory driven network activity. Next we discuss the functional role of transient cortical structures and cell types in the generation of early activity patterns and in the activity-dependent maturation of local and large-scale cortical networks. Finally, we present an outlook on the models and techniques to study the cellular and network mechanisms underlying neuronal activity in the developing cerebral cortex.